Pengaruh Pemberian Kompres Hangat Terhadap Penurunan Nyeri Disminore Remaja Putri Di SMP Takhasus Alquran Wonosobo - Khoirun Nisa’; Kamidah Kamidah (Pusat Riset dan Inovasi Nasional, 2023)
Backgound: Dysmenorrhea is a medical condition during menstruation that hinders women from doing activity because of soreness or pain in the abdomen or pelvis. Dysmenorrhea can be found in some women in different ages including teenage girls. In Indonesia the rate of dysmenorrhea is approximately around 64,25% consisting of 54,89% of primary dysmenorrhea and 9,36% of secondary dysmenorrhea. If it is not appropriately treated, the symptoms could interrupt daily activities. A non-pharmacology therapeutic method that alleviates pain can be applied using hot water compression (37-40C) for about 15 minutes. Research Objective: The research purpose is to investigate and discover the effect of hot water compression method for the teenage girls at SMP Takhasus Al-Quran Wonosobo. Research Methods: This research employs a pre-experimental design (Pre-test – Treatment – Post-test). The data was collected from respondents that were made up of 33 populations and 30 sampling of teenage girls using random sampling methods before it was analysed by Wilcoxon signed test. Result: The average scale of pain before treatment by hot water compress was 5,67, while after the care, were decreasing to 4,03 scale. Conclusion: Hot water compress has a positive response in decreasing the dysmenorrhea pain for teenage girls at SMP Takhasus Al-Quran Wonosobo.